TEORI SURPLUS BERSIH: VALUASI PERUSAHAAN BERDASARKAN DATA AKUNTANSI - WIRAMA, DEWA GEDE (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 3 No 2 (2008), 2008)
Fundamental accounting research under measurement perspective regained researchers’ consideration following the publications of Ohlson (1995) and Feltham and Ohlson (1995) valuation models. While fundamental researches before Ball and Brown (1968) were mostly focusing on the determination of the “correct” income number in economic sense, current fundamental researches are more about firm valuation based on accounting numbers.Ohlson (1995) and Feltham and Ohlson (1995) valuation models are based on clean surplus theory. The theory considers accounting as a wealth creation and distribution recording system, and thus provides the base of the relation between firm value and accounting numbers. Based on neoclassical concept of value, clean surplus theory states that a firm value is equal to its book value plus the present value of expected abnormal earnings, termed as goodwill. Based on that relation, Ohlson (1995) formulated a closed-form valuation model that explain firm value based only on current and one period ahead book value and earnings. Feltham and Ohlson (1995) is an attempt to generalized Ohlson (1995) for accounting conservatism and growth.Clean surplus theory is now used as an alternative to CAPM in estimating cost of capital and risk. While Feltham and Ohlson (1995) model seems to have a misspecification for conservatism, the empirical validity of Ohslon (1995) model has been tested with relatively satisfactory results. The model is deemed to be valid as it explains stock prices. The test results, however, also suggest that there is plenty of room to make further contribution in refining the theory. Further research suggestion includes, among others, examination of factors affecting abnormal earnings and the validity of the theory in general, more accurate specification of LID, and enhancement of Feltham and Ohlson (1995) model in dealing with accounting conservatism and growth.
Keywords: wealth creation, accounting number, clean surplus, valuation model, empirical validity